The Agricultural Groundwater Revolution: Opportunities and Threats to Development - Giordano, Mark (CABI, 2014)
Over the last 50 years groundwater development has played a fundamental role in agricultural production in many parts of the developing world. For example, groundwater now accounts for approximately 50% of all irrigation supply in South Asia and perhaps two-thirds of supply in the grain belts of North China. The rapid growth in use in these and other regions has played a vital role in maintaining the rise in grain output associated with the Green Revolution, transforming production and livelihood strategies for millions of small farmers and providing food to growing urban centres.